Combined effect of photoperiod and stocking density on the welfare of greater amberjack (Seriola dumerili) - Barreto-Bailet, Michelle; Jerez, Salvador; García-Beltrán, José M.; Felipe, Beatriz C.; Galindo, Ana; Chaves-Pozo, Elena; Martín, M. Virginia (Frontiers in Marine Science, 2025)
Seriola dumerili is a fast-growing species under culture conditions with significant potential for diversification of marine aquaculture. The interest in this species raises new challenges for its culture, such as the design of suitable procedures and appropriate conditions in order to determine the adequate operational parameters for animal welfare, which will also allow the generation of management protocols that guarantee these conditions. These parameters include stocking density and photoperiod, which can be decisive in the welfare of the farmed fish. Therefore, the overall objective of this study was to investigate the combined effect of different culture conditions (stocking density and photoperiod) on different biochemical indicators of stress, including plasma and skin mucus parameters, immune response, oxidative damage and antioxidant response in S. dumerili. Adult specimens were divided into four groups and maintained under two stocking densities (2.5 kg m-³ and 5.0 kg m-³) and two photoperiods (12L:12D and 16L:8D) (n=9 for each condition). The results showed that after 30 days, there were no negative effects on the growth performance of fish stocked at higher density or long photoperiod. There were also no changes in plasma stress markers or immune parameters. However, under long photoperiod, higher cortisol levels were found in skin mucus, along with alterations in antioxidant activities in key tissues such as liver or gills, as well as, lipid peroxidation in liver, brain and muscle, indicating some degree of oxidative stress. In contrast, variations in different stocking densities did not lead to significant alterations in these parameters. This study offers new insights into the mechanisms involved in the stress response of S. dumerili, aiming to evaluate different culture conditions and determine stress-inducing factors for this species.